Oncogenic enhancer of zeste homolog 2 is an actionable target in patients with non‐small cell lung cancer. (27th August 2019) - Shi, Bin; Behrens, Carmen; Vaghani, Viralkumar; Riquelme, Erick Marcelo; Rodriguez‐Canales, Jaime; Kadara, Humam; Lin, Heather; Lee, Jack; Liu, Hui; Wistuba, Ignacio; Simon, George
Abstract: Background: The aims of this study were to investigate the link between enhancer of zeste homolog 2 (EZH2) and histone deacetylase (HDAC) in preclinical studies and in human lung cancer tissue microarrays. Methods: Enhancer of zeste homolog 2 and HDAC1 mRNA expression in two lung adenocarcinoma (LUAD) datasets (MDACC and TCGA) were correlated with patient outcomes. We evaluated the association of EZH2 and HDAC1 expression with response to the HDAC1 inhibitor, suberoylanilide hydroxamic acid (SAHA). The response to SAHA was assessed at baseline and after alteration of EZH2 or HDAC mRNA expression in LUAD cell lines. Results: Direct correlation was found between EZH2 and HDAC1 expression ( P < 0.0001). When EZH2 expression was knocked down‐ or upregulated, there was a corresponding decrease or increase in expression of HDAC expression, respectively. Cell lines with high EZH2 expression responded to SAHA treatment with a mean inhibition rate of 73.1% compared to 43.2% in cell lines with low EZH2 expression ( P < 0.0001). This correlation was confirmed in non‐small cell lung cancer (NSCLC) specimens from MDACC (Spearman's correlation r = 0.416; P < 0.0001) and TCGA datasets ( r = 0.221; P < 0.0001). Patients with high EZH2 and high HDAC1 expression in stage I NSCLC specimens of both datasets had the lowest survival compared to the patients with low expression of either or both markers. Conclusion: Our findings show that overexpression of EZH2 is a negative prognostic indicator. Increased EZH2 expression predicts for response to HDAC inhibitors and thus could serve as a biomarker for selecting NSCLC patients for treatment with HDAC inhibitors. Abstract : Overexpression of EZH2 is a negative prognostic indicator. Increased EZH2 expression predicts for response to HDAC inhibitors and thus could serve as a biomarker for selecting NSCLC patients for treatment with HDAC inhibitors.